The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17358/ijbe.4.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Investor Sentiment Impact in Indonesia Composite Stock Price Index Return Volatility

Abstract: The Composite Stock Price Index (IHSG) is an index used as an indicator of stock price movements on Indonesia Stock Exchange and reference of capital market activities. Stock securities have high risk because they do not have maturity such as bonds so volatility is one of the important things in stock investment. Investor sentiment is one of many external factors that affecting stocks volatility. Investor sentiment is one of behavioral finance assumptions which may cause systematic risk with noise so it affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…In other words, the magnitude effect of sentiment on the index is the same for good news and bad news. This finding is supported by the research of Baker et al (2012); Ramli et al (2016), Widhiarti et al (2018); and Rupande et al (2019). The authors argued that individual investor sentiment influences stock returns.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In other words, the magnitude effect of sentiment on the index is the same for good news and bad news. This finding is supported by the research of Baker et al (2012); Ramli et al (2016), Widhiarti et al (2018); and Rupande et al (2019). The authors argued that individual investor sentiment influences stock returns.…”
Section: Resultssupporting
confidence: 69%
“…In the ASEAN front, using the excess returns of Indonesian stocks, Widhiarti et al (2018) confirmed the significant effect of investor sentiment on excess returns. Ramli et al (2016) found that herding occurs in the Indonesian stock exchange owing to information asymmetry between domestic and foreign investors.…”
Section: Introductionmentioning
confidence: 71%
“…Empirical evidence in Indonesia on sentiment based on news on the internet found that sentiment cannot be used to predict returns (Rizkiana et al, 2019). Another study in Indonesia stated that sentiment with proxy tendency business index significantly affects excess return (Widhiarti et al, 2018). Research in Indonesia on sentiment is conducted using proxies other than market information, so sentiment research with market data is necessary to enrich empirical evidence about sentiment Empirical evidence of 52-week highs is more done in developed countries or countries with high liquidity financial markets, such as the United States, Taiwan, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Investor tetap akan membeli saham pada saat harga saham meningkat. Sejalan dengan yang ditemukan oleh Widhiarti (2018), dimana perilaku investor di Indonesia masih cenderung berspekulasi pada kenaikan harga, sehingga sering melewatkan faktorfaktor fundamental yang ada. Selain itu, proksi yang digunakan adalah ROE, dimana terdapat beberapa kasus perusahaan memiliki nilai ekuitas yang negatif dan mengalami kerugian, tetapi nilai pembaginya akan menjadi positif.…”
Section: Pembahasan Pengaruh Profitabilitas Terhadap Return Sahamunclassified